Partisipasi Politik Perempuan di DPRD Kabupaten Raja Ampat 2009-2014 - Helena Helena (POLITIK, 2014)
AbstrakPartispasi politik perempuan di Kabupaten Raja Ampat merupakan perwujudan dari Undang-undang Republik Indonesia Nomor 12 Tahun 2003 tentang Pemilihan Umum Anggota DPR, DPD, dan DPRD. Dengan metode deskkriptif dan pendekatan kualitatif, maka ditemukan sejumlah hambatan dan peluang keterwakilan perempuan dalam DPRD Kabupaten Raja Ampat. Keywords: partisapasi politik, perempuan, Kabupaten Raja Ampat AbstractPolitical participation of women in Raja Ampat Regional Government is the embodiment of Indonesia’s constitution Number 12 in 2003 towards the Election of House of Representatives, Regional Representative Council and Regional Government members. By using descriptive methods and qualitative approaches, so that can be found a number of obstacles and opportunities for women’s representation in Raja Ampat Regional Government. Keywords: political participation, women, Raja Ampat